Monitoring of qualifications and employment in Austria : an empirical approach based on the Labour Force Survey - Lassnigg, Lorenz [Verfasser]; Vogtenhuber, Stefan [Verfasser] (My University, 2011)
"The empirical approach referred to in this article describes the relationship between education and training (ET) supply and employment in Austria; the use of the new ISCED (International Standard Classification of Education) fields of study variable makes this approach applicable abroad. The purpose is to explore a system that produces timely information on how the specialised and layered supply of initial vocational education and training (VET) is reflected in employment structures. This is done by 'screening' potential risks and opportunities related to ET specialisations, and by comparing a set of indicators across the whole ET supply (from simple occupations to higher education). The approach is based on theory of 'constructivist' knowledge management, and its intent is to provide input for reflection and learning among stakeholders regarding the empirical relationship between ET supply and demand. Consequently, the results do not aspire to offer 'hard evidence', but should instead draw attention to those areas of risk which merit further inquiry. The monitoring system comprises two parts: (1) a comprehensive classification of VET supply; and (2) a multifaceted set of indicators and measurement procedures. The latter is split into three sections: (a) demographics and gender; (b) employment, unemployment and income; and (c) competences, occupations and trades. In each section a number of indicators is defined to compare the risks and opportunities for the 44 programme categories of VET and higher education in several dimensions - for example, the relation of new entrants to potential replacement demand; specific aspects of employment and unemployment measures; relative incomes; and skills utilisation and projections of future demand. The results show interesting patterns of corresponding and contrasting relations between ET and employment for VET programmes. There are limitations, given the small sample size of the Labour Force Survey, while there is also room for greater methodological sophistication." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2.1 Westeuropa; Beziehung Bildungssystem Beschäftigungssystem; Monitoring; Arbeitskräfteangebot; Qualifikation; Fachkräftebedarf; Österreich